What is the impact of food reformulation on individuals' behaviour, nutrient intakes and health status? A systematic review of empirical evidence. (6th October 2020) - Gressier, Mathilde; Swinburn, Boyd; Frost, Gary; Segal, Alexa B.; Sassi, Franco
Summary: Food reformulation aimed at improving the nutritional properties of food products has long been viewed as a promising public health strategy to tackle poor nutrition and obesity. This paper presents a review of the empirical evidence (i.e., modelling studies were excluded) on the impact of food reformulation on food choices, nutrient intakes and health status, based on a systematic search of Medline, Embase, Global Health and sources of grey literature. Fifty‐nine studies (in 35 papers) were included in the review. Most studies examined food choices ( n = 27) and dietary intakes ( n = 26). The nutrients most frequently studied were sodium ( n = 32) and trans fatty acids (TFA, n = 13). Reformulated products were generally accepted and purchased by consumers, which led to improved nutrient intakes in 73% of studies. We also conducted two meta‐analyses showing, respectively, a −0.57 g/day (95%CI, −0.89 to −0.25) reduction in salt intake and an effect size for TFA intake reduction of −1.2 (95% CI, −1.79 to −0.61). Only six studies examined effects on health outcomes, with studies on TFA reformulation showing overall improvement in cardiovascular risk factors. For other nutrients, it remains unclear whether observed improvements in food choices or nutrient intakes may have led to an improvement in health outcomes.